2019
DOI: 10.1159/000499200
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Serum Soluble Klotho Levels and Echocardiographic Parameters in Patients on Maintenance Hemodialysis

Abstract: Background: Cardiovascular disease is the leading cause of morbidity and mortality in maintenance hemodialysis (MHD) patients. Uremic cardiomyopathy, characterized by myocardial hypertrophy and fibrosis, has a significant contribution to these adverse cardiac outcomes. The protective effect of soluble Klotho (s-Klotho) on myocardial damage was demonstrated in in vitro and animal experiments. However, data from MHD patients is limited. The present study was designed to identify potential correlations between ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 35 publications
(44 reference statements)
1
19
0
Order By: Relevance
“…Recent data prefer to pay more attention on the role of Klotho in CKD-induced LVH. It has been reported that maintenance hemodialysis patients with lower circulating sKlotho levels were more often associated with larger interventricular septal thickness and greater ratios of interventricular septal thickness and posterior wall thickness, which are typical indicators of LVH in patients [64]. Consistently, in a survey of 86 patients with CKD, we found that increased left ventricular mass was more apparent in patients with low Klotho level [6].…”
Section: The Role Of Klotho In Left Ventricular Hypertrophysupporting
confidence: 87%
“…Recent data prefer to pay more attention on the role of Klotho in CKD-induced LVH. It has been reported that maintenance hemodialysis patients with lower circulating sKlotho levels were more often associated with larger interventricular septal thickness and greater ratios of interventricular septal thickness and posterior wall thickness, which are typical indicators of LVH in patients [64]. Consistently, in a survey of 86 patients with CKD, we found that increased left ventricular mass was more apparent in patients with low Klotho level [6].…”
Section: The Role Of Klotho In Left Ventricular Hypertrophysupporting
confidence: 87%
“…In the same study, LVEF, LVMI, and LA were not associated with sKlotho. Other echocardiographic parameters do not seem to support IVST elevation in their study 13 …”
Section: Discussionmentioning
confidence: 67%
“…In a study conducted with 105 hemodialysis patients, a significant relationship was found between low sKlotho and high IVST and IVST/LVPWT. Zhang et al divided the patients into four groups according to sKlotho values in their study and found an independent relation and negative correlation between low sKlotho and IVST, but they did not find a significant relationship between sKlotho and LVEF, LVMI, and LA 13 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Klotho is also expressed in vascular tissue, and Klotho deficiency in mice caused severe calcification in vascular and soft tissues [ 31 ]. In clinical studies, lower sKlotho levels were shown to be closely linked to increased artery calcification, coronary artery calcification, and valve calcification in dialysis patients [ 32 34 ]. Calcification in vascular or soft tissue can most certainly greatly increase detrimental outcomes in MHD patients.…”
Section: Discussionmentioning
confidence: 99%